Implementasi Bimbingan Karir Siswa Kurikulum Merdeka Belajar di SMAN 21 Kota Bekasi - Ismi Ismi Izzati; Siti Hajar (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The aim of the research is to determine the implementation of career guidance activities for students at SMAN 21 Bekasi City which uses the Merdeka Curriculum. Qualitative research with narrative descriptions was used by researchers to analyze the problems of this research. The samples studied were the Principal, Deputy Principal for Curriculum and Student Affairs, Class XI BK teachers, parents and Class XI students. The tools used to collect data are open interviews, observation and documentation. Data collection, reduction, presentation and conclusion drawing are used by researchers to analyze the data. Data validity checking techniques use credibility tests, linkage tests, certainty tests, and transferability tests. The results of the research show that problems arise in the implementation of career guidance, namely: 1) First, limited facilities with a value of 20%, second with a value of 10% including the problem of students choosing majors that do not match their grades, students are still confused about choosing a major, economic difficulties, Inappropriate choice of major, insufficient budget, low parental participation, and low student motivation to study. The lowest percentage was 5%, namely students did not want counseling and guidance and counseling teachers had not explained the career guidance material optimally. 2) Implementing career guidance for students in the independent learning curriculum has 4 stages, namely mapping talents and interests, implementing guidance, assessing career guidance, and reflecting on the results of the career guidance assessment.